(untitled) (World of finance, 2022)
Introduction. The transition of most countries of the world to the construction of a carbon-neutral economy in 2060 make the Ukrainian authorities with the task to accelerate the reform of the environmental financing system. But in this aspect, our country still lags behind the environmental requirements of European Union, to which countries Ukraine exports a significant part of its products. Therefore, it is important to study the experience of EU countries on this issue and implement the best of it in Ukraine The purpose of the article is to determine the problems of environmental taxation and financing measures for environmental protection at the level of territorial communities in Ukraine and to develop recommendations for their solution, taking into account the experience of EU countries. Methods. General and special methods were used in the research, in particular – analysis and synthesis, induction and deduction, logical generalization, abstraction. Results. The structure of expenditures of the Consolidated Budget of Ukraine for environmental protection by types of budgets was analyzed. It was determined that the main sources of financing environmental protection measures are the funds of the state and local budgets, international organizations; funds received from the lease of water objects located within the boundaries of settlements of communities and others. It was revealed that the main source of income for environmental protection funds is the environmental tax, which the state does not always use for its intended purpose. The experience of environmental taxation in the EU countries was studied and the ways of its introduction at the level of territorial communities in Ukraine were substantiated. Conclusions. Using the experience of the EU countries, it is proposed to: separate the carbon tax and use the revenues from it for investments in climate projects at the local level; at the level of territorial communities, implement co-financing and private-public partnership in the environmental sphere, providing appropriate financial incentives for enterprises and institutions, also financially encouraging them to carry out energy-saving measures and reduce greenhouse gas emissions; introduction "green" public procurement; use local "green" bonds to finance "green" projects at the local level.